Perception of Conventional Cigarettes and Vaping among Smokers and Nonsmokers: A Cross-sectional Study - Gunardi, Indrayadi; Amtha, Rahmi; Hartanto, Firstine Kelsi; Falatehan, Niko; Heriandi, Alyah; Kurniawan, Angelita Victoria; Nadiah, Najla; Poedjiastoeti, Wiwiek; Andrijanto, Andrijanto; Sari, Elizabeth Fitriana (Journal of Dentistry Indonesia, 2025)
Objectives: The growing popularity of vaping has introduced additional challenges, as potential health risks are still under investigation. Exploring differences in smoking perceptions between smokers and non-smokers could provide valuable insights into smoking behavior and inform effective intervention strategies. This study aimed to evaluate and compare the perceptions of smoking, specifically vaping and conventional cigarette use, among young adult smokers and non-smokers. Methods: An analytical cross-sectional design was employed, with 542 university students included through random sampling, using a questionnaire consisting of 8 items. Data were analyzed using the Kruskal-Wallis test and Rasch model analysis. Results: Of the subjects, 259 (48%) used vapes and 283 (52%) were non-smokers. The age distribution was as follows: under 19 years (13.51% vs 38.87%), 19-20 years (46.33% vs 32.16%), and over 21 years (40.15% vs 28.98%). The Wright map indicated perceptual differences between smokers and non-smokers, with smokers showing greater agreement with smoking perceptions (>1 logit). Significant differences (p < 0.001) were found in each item across all groups. Conclusion: The study identified distinct perceptual differences regarding smoking between smokers and non-smokers, with smokers having a more favorable perception towards smoking. Non-smokers generally showed a stronger aversion to conventional cigarettes compared to electronic ones. These findings underscore the importance of developing targeted smoking cessation programs that address the specific perceptions and attitudes of both groups.